(untitled) (Revista Científica Compendium, 2023)
The research is based on a descriptive field study aimed at designing guidelines for the optimization of administrative management in the company Cereales Venezolanos CEREVEN C.A., located in Barquisimeto, Lara State, Venezuela. It was carried out in the first half of the year 2023, taking into account the dimensions of administrative management: Planning, Organization, Direction and Control. Two surveys were designed: one addressed to coordinators and supervisors; and the other to managers and chiefs. The organization has favorable elements for the implementation of managerial administrative strategies. However, there are flaws in the communication processes and in the internal control system. It is recommended that management training policies be implemented in order to implement professional development programs by establishing partnerships with universities in the region.